COMPARISON BETWEEN TWO PROTOCOLS OF AEROBIC TRAINING FOR REDUCING THE PERCENTAGE OF FAT (Fiep Bulletin - online, 2011)
Aerobic exercises are those that relate to the use of oxygen and metabolic adaptations in skeletal muscle. At low intensities, free fatty acids are mobilized from the periphery to the supply of most of the substrate, helping maintain the balance of fats. However, intermittent high-intensity exercise resulted in a higher reduction of skinfold thickness. The results were statistically analyzed using the nonparametric McNemar test (paired observations) for comparisons between seasons (pre and post) with significance taken at 5%. The aim of this study was to compare efficacy of two training methods in reducing body fat of 20 males, aged 27.75 ± 4.25 years. Although the protocols have reduced the positive variables, the tests performed at high intensity and intermittently obtained better results in all parameters compared with aerobic exercises for mild to moderate and long duration.
Keywords: aerobic exercise; fatty acids; skinfold